Oesophageal mucosal changes in patients with varices. Issue 11 (November 1983) - Spence, R A; Sloan, J M; Johnston, G W; Greenfield, A
Abstract : Histological examination of oesophageal rings removed at transection for varices reveals dilated intraepithelial blood filled channels. These are present in all oesophageal rings removed at transection for varices. A comparison has been made between rings removed from variceal patients with oesophageal rings removed during resections for oesophageal and gastric tumours. Although a small number of non-varices patients had intraepithelial channels they were significantly larger and more numerous in the varices patients (p less than 0.01). Similarly, the area and number of dilated subepithelial channels (just beneath the epithelium) and the area of lamina propria channels were significantly greater in the varices patients (p less than 0.05). Depth of papillae and thickness of the squamous epithelium were also significantly greater in the varices group (p less than 0.05, p less than 0.01 respectively). Under electron microscopy the channels were lined with flattened cells which were not typical of endothelial cells but stained positively for Factor VIII related antigen using indirect immunofluorescence. These channels may correspond to the cherry-red spots seen on endoscopy and may have a role in the pathogenesis of variceal haemorrhage.